2004
DOI: 10.1038/nm996
|View full text |Cite
|
Sign up to set email alerts
|

Transducible TAT-HA fusogenic peptide enhances escape of TAT-fusion proteins after lipid raft macropinocytosis

Abstract: The TAT protein transduction domain (PTD) has been used to deliver a wide variety of biologically active cargo for the treatment of multiple preclinical disease models, including cancer and stroke. However, the mechanism of transduction remains unknown. Because of the TAT PTD's strong cell-surface binding, early assumptions regarding cellular uptake suggested a direct penetration mechanism across the lipid bilayer by a temperature- and energy-independent process. Here we show, using a transducible TAT-Cre reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

60
1,452
10
6

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,531 publications
(1,528 citation statements)
references
References 30 publications
60
1,452
10
6
Order By: Relevance
“…Many therapeutic cargo molecules have been successfully delivered into cells via CPPs including proteins, peptides, si-RNA, DNA, and others (van den Berg and Dowdy, 2011;Zorko and Langel, 2005). TAT-BH4 and TAT-Bcl-XL inhibited sepsis-induced apoptosis of lymphocytes in vivo (Hotchkiss et al, 2006) and TAT-Cre was used to generate conditional knock-out mice (Wadia et al, 2004). Polyarginine (11R)-conjugated VIVIT peptide, which is a specific NFAT inhibitory peptide, was able to inhibit graft rejection of allogeneic islet transplantation in mice (Noguchi et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Many therapeutic cargo molecules have been successfully delivered into cells via CPPs including proteins, peptides, si-RNA, DNA, and others (van den Berg and Dowdy, 2011;Zorko and Langel, 2005). TAT-BH4 and TAT-Bcl-XL inhibited sepsis-induced apoptosis of lymphocytes in vivo (Hotchkiss et al, 2006) and TAT-Cre was used to generate conditional knock-out mice (Wadia et al, 2004). Polyarginine (11R)-conjugated VIVIT peptide, which is a specific NFAT inhibitory peptide, was able to inhibit graft rejection of allogeneic islet transplantation in mice (Noguchi et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…FACS analysis following trypsin treatment indicated a relatively slow rate of uptake, comparable to that of classical markers of endocytosis. Since then, many other studies have also observed inhibition of cellular uptake at 4°C and with chemical means that induce energy depletion, indicating an energy-dependent process as the major route for the internalization of cell-penetrating peptides [27][28][29][30][31][32][33].…”
Section: Direct Translocation Endocytosis: An Either/or Discourse?mentioning
confidence: 99%
“…Moreover, direct translocation of TAT peptide into the interior of giant unilamellar vesicles (GUVs) was likewise shown to depend on a minimum threshold amount of membrane PE content [57]. As another example, high cholesterol membrane content has been shown to accompany each type of receptor-independent endocytotic pathway implicated in cell-penetrating peptide uptake, including lipid raft-mediated caveolae and macropinocytosis [32,83] as well as clathrin coated pit endocytosis [84]. We find that the presence of cholesterol at typical eukaryotic values will drastically enhance the ability of a membrane to form negative Gaussian curvature necessary for these mechanisms [82].…”
Section: The Arginines In the Tat Peptide Generate Negative Gaussian mentioning
confidence: 99%
“…These findings suggest that the uptake of TAT–THS–Atto647 by PC‐3 and of THS–Atto647 by U87 cells follow different pathways. Taking into account that the general uptake mechanisms of TAT and its diverse cargo are still under scientific debate,27 it cannot be concluded whether TAT–THS enters the cells through the endosomal pathway and escapes the endosome, or if it reaches the cytosol by macropinocytosis 28. Nevertheless, these results confirm that TAT can translocate relative large proteins into cells that would otherwise not internalize these proteins 29…”
Section: Resultsmentioning
confidence: 99%